Measurement of triple-gauge-boson couplings of the W boson at LEP - Dova, María Teresa (1999)
We report on measurements of the triple-gauge-boson couplings of the W boson in e+e- collisions with the L3 detector at LEP. W-pair, single-W and single-photon events are analysed in a data sample corresponding to a total luminosity of 76.7 pb-1 collected at centre-of-mass energies between 161 GeV and 183 GeV. CP-conserving as well as both C- and P-conserving triple-gauge-boson couplings are determined. The results, in good agreement with the Standard-Model expectations, confirm the existence of the self coupling among the electroweak gauge bosons and constrain its structure.